A Community-Based Early Childhood Development Center Platform Promoting Diversified Diets and Food Production Increases the Mean Probability of Adequacy of Intake of Preschoolers in Malawi: A Cluster Randomized Trial. Issue 2 (14th October 2019) - Gelli, Aulo; Nguyen, Phuong Hong; Santacroce, Marco; Twalibu, Aisha; Margolies, Amy; Katundu, Mangani
ABSTRACT: Background: Young children in Malawi consume low-quality diets lacking micronutrients critical for their development. Objective: To evaluate the impact of an agriculture and nutrition behavior change communication (BCC) intervention implemented through community-based childcare centers on the nutrient adequacy of diets of children living in food-insecure settings in Malawi. Methods: A cluster randomized trial was undertaken in 60 community-based childcare centers, including 1248 children aged 3–6 y. Nutrient intakes were estimated using interactive, multipass 24-h recall. Dietary adequacy was estimated through the probability of adequacy (PA) and mean probability of adequacy (MPA) of 11 micronutrients. Impacts were assessed by difference-in-difference (DID) estimates, adjusted for geographic clustering and child age and sex. Results: Intervention groups were similar for most baseline characteristics. Loss to follow-up was low (7% over a 12-mo period) and participation in the intervention was high (>90% enrollment and 80% attendance during the 5 d before the survey). Positive impacts were found for the PA of several individual micronutrient intakes: vitamin A [DID: 9 percentage points (pp), SE 3 pp], vitamin C (14 pp, SE 3 pp), riboflavin (11 pp, SE 3 pp), zinc (8 pp, SE 3 pp), and for the MPA for the 11 nutrients considered (5 pp, SE 1 pp). These impacts were driven by effects on younger children (aged 3–4 y). Conclusions: Using a preschool platform to implement a nutrition-sensitive BCC intervention is an effective strategy to improve the adequacy of micronutrient intake of preschool children in food-insecure settings. The trial was registered at ISCRCTN as ISCRCTN96497560.